The Impact of Delay Announcements on Hospital Network Coordination and Waiting Times - Dong, Jing; Yom-Tov, Galit; Yom-Tov, Elad (Management Science, 2018)
We investigate the impact of delay announcements on the coordination within hospital networks using a combination of empirical observations and numerical experiments. We offer empirical evidence that suggests that patients take delay information into account when choosing emergency service providers and that such information can help increase coordination in the network, leading to improvements in the performance of the network, as measured by emergency department wait times. Our numerical results indicate that the level of coordination that can be achieved is limited by the patients’ sensitivity to waiting, the load of the system, the heterogeneity among hospitals, and, importantly, the method hospitals use to estimate delays. We show that delay estimators that are based on historical averages may cause oscillation in the system and lead to higher average wait times when patients are sensitive to delay. We provide empirical evidence that suggests that such oscillations occur in hospital networks in the United States.